Energy decay rate for the wave equation with variable coefficients and boundary source term. Issue 11 (18th August 2021) - Ha, Tae Gab
Abstract : In this paper, we consider the wave equation with variable coefficients and boundary source term. This work is devoted to prove the uniform energy decay rates of the wave equation with variable coefficients applying the Riemannian geometry method and modified multiplier method. This result gives us to classify the energy decay rate depending the growth near zero on the damping term.